Vimentin as an Integral Regulator of Cell Adhesion and Endothelial Sprouting. (May 2014) - Dave, Jui M.; Bayless, Kayla J.
Abstract Angiogenesis is a multistep process that requires intricate changes in cell shape to generate new blood vessels. IF are a large family of proteins that play an important structural and functional role in forming and regulating the cytoskeleton. Vimentin, a major type III intermediate filament protein is expressed in endothelial and other mesenchymal cells. The structure of vimentin is conserved in mammals and shows dynamic expression profiles in various cell types and different developmental stages. Although initial studies with vimentin‐deficient mice demonstrated a virtually normal phenotype, subsequent studies have revealed several defects in cell attachment, migration, signaling, neurite extension, and vascularization. Regulation of vimentin is highly complex and is driven by posttranslational modifications such as phosphorylation and cleavage by intracellular proteases. This review discusses various novel functions which are now known to be mediated by vimentin, summarizing structure, regulation and roles of vimentin in cell adhesion, migration, angiogenesis, neurite extension, and cancer. We specifically highlight a pathway involving growth factor‐mediated calpain activation, vimentin cleavage, and MT1‐MMP membrane translocation that is required for endothelial cell invasion in 3D environments. This pathway may also regulate the analogous processes of neurite extension and tumor cell invasion.